A step back for Women’s Rights: Reviving the Issue of the Right to abortion in the 21st century - Grbović, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Nowadays, the right to abortion has inevitably become not only a legal, but also a political and religious issue, which has been the subject of numerous discussions for years, both in terms of its moral character and legal treatment. Unfortunately, the fact is that no consensus has yet been reached on the right to abortion, which is also emphasized by the advocates of the "pro-life" and "pro-choice" movements. Analyzing international documents as well as court practice, the author expresses her concern about the current situation in certain countries, which, due to the restrictive interpretation of the right to abortion, leave women without adequate and complete legal protection.